CORRELATED CHANGES IN GRIP STRENGTH AND COGNITION: MULTI-STUDY RESULTS BASED ON BIVARIATE LINEAR GROWTH MODELING. (11th November 2018) - Zammit, A; Piccinin, A M; Robitaille, A; Clouston, S; Muniz-Terrera, G; Koval, A; Hofer, S M
Abstract: We investigated the association between rates of change in grip strength and indicators of different domains of cognitive function (mental status, processing speed, attention and working memory, perceptual reasoning, verbal ability, and learning and memory) within a multiple-study comparative framework. Bivariate growth models stratified by gender were conducted across nine studies affiliated with the Integrative Analysis of Longitudinal Studies of Aging and Dementia research network. We summarized results using meta-analysis. We found consistent moderate-to-strong associations between grip strength and each cognitive domain for both males and females. Meta-analysis showed an overall average correlation coefficient of 0.55 (95%CI = 0.44 – 0.56), and a range spanning from -0.49 for Learning and Memory in males to 0.92 for Processing Speed in males. Our coordinated meta-analysis provided evidence for a consistent association between changes in grip strength and changes across a broad range of cognitive functioning.